Determinants of Investment Attractiveness of Polish Special Economic Zones - Tomasz Dorożyński; Janusz Świerkocki; Wojciech Urbaniak (Entrepreneurial Business and Economics Review)
Objective: The objective of this article is to explain why some Special Economic Zones in Poland have attracted more foreign and domestic investment than others.